Pendidikan Kewarganegaraan Digital sebagai Respon terhadap Cyberbullying di Indonesia - Octavia Wulandari; Arif Surya Volta; Marzuki Marzuki; Muhammad Muslim Hidayatulloh (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
This study aims to analyze the integration and implementation of Digital Citizenship Education (DCE) in Indonesia's national curriculum as a preventive measure against the increasing cases of cyberbullying among teenagers. The study was conducted through a literature review of curriculum policy documents and relevant journal articles. The results show that cases of cyberbullying in Indonesia continue to increase, especially among young people who use social media. Although the government has strengthened regulations through revisions to the Electronic Information and Transactions Law, law enforcement has not been effective enough without the support of digital values and ethics education in schools. An analysis of the Merdeka Curriculum reveals that PKD is not yet a separate subject, but is integrated into certain subjects such as Informatics, Religious Education and Morality, and Pancasila Education, and is implemented across the curriculum. This integration is still implicit and focuses on digital literacy. Therefore, it is necessary to develop a systematic and applicable PKD learning model, emphasizing four main elements in preventing cyberbullying, namely digital communication, digital literacy, digital etiquette, and digital law. These four elements are important in shaping the character of digital citizens who are smart, ethical, and responsible. Keywords: Digital Citizenship Education, Cyberbullying, Indonesia